Association between a national public health campaign for physical activity for patients with chronic diseases and the participation in Phase III cardiac rehabilitation in Luxembourg. (February 2021) - Lion, Alexis; Tchicaya, Anastase; Theisen, Daniel; Delagardelle, Charles
Highlights: National public health campaign may increase participation to Phase III cardiac rehabilitation. National public health campaign increases visibility of a website displaying the Phase III cardiac rehabilitation. A more integrated and synergized strategic approach may help to sensitize the patients. Abstract: Background: A 2-stage national campaign promoting physical activity for patients with chronic diseases (including cardiovascular disease) was implemented in the Grand-Duchy of Luxembourg in 2018. The first stage consisted of national TV and radio advertisements broadcasted from June 15, 2018 to July 29, 2018. The second stage was a promotional mail sent to all medical doctors on September 3, 2018. This study investigated the association between this campaign and the participation of cardiac patients in Phase III cardiac rehabilitation as well as the visibility of a dedicated website (www.sport-sante.lu ). Methods: The daily numbers of participants in the classes of the Phase III cardiac rehabilitation and the visits on www.sport-sante.lu were collected from January 1, 2016 to December 31, 2018. Segmented regression analysis was used to assess the association between the promotional campaign and the participation in the Phase III cardiac rehabilitation as well as the website visibility. Results: The baseline participation rate, which was 30 participants/day, increased temporarily by 11 (p = 0.0267) and 18 (p = 0.0030) participants/day after the first and second stages of the campaign, respectively. The baseline visit rate on www.sport-sante.lu, which was 12 visits/day, increased temporarily by 20 (p < 0.0001) and 15 (p = 0.0002) visits/day after the first and second stages of the campaign, respectively. Conclusions: The national public health campaign was associated with a limited increased participation in the Phase III cardiac rehabilitation and the website visibility. However, no conclusion can be drawn about causality due to the long and difficult process from health promotion to patient's behavior change.